Diferenças individuais no comportamento forrageiro de Polistes versicolor Olivier, 1872 (Vespidae, Polistinae) - Brocanelli, Felipe Gonçalves [UNESP] (2015)
Polistes versicolor is one of the most studied and known species of its genus in Brazil. It occurs throughout the national territory, is well adapted to human environment, lacks morphological caste differences and thus its hierarchical system is mainly based on behavioral features, distinguished by dominance/subordination acts. For feeding their larvae mainly with animal protein (most of them Lepidoptera caterpillars), Polistes wasps show great potential in biological control programs, possibly preying on some pests that attack economically important crops to men. This way, this study aimed to assess some biological features and processes related to hierarchy formation on P. versicolor colonies as well, in order to see their relationship with foraging activities. This work's outcomes show what many other studies have seen; queens found their nests either alone or in groups, and nest foundations are asynchronic, which can occur from August to April. One winter aggregation was observed during the cold season (May - August). Data collection on hierarchy formation and foraging behavior in some nests ensured us to say that the dominant wasp is one of the most aggressive individuals, and also spends most of its time at the comb, without leaving it. Relative age of these queens varied between nests; in some cases they were the oldest, in some the youngest and in some they presented intermediate ages. The trips executed by foragers allowed us to affirm that each resource shows a trend to be collected in specific periods along the day, depending on the colony needs. In average, water trips lasted less than other materials, while returns with animal protein lasted longer. It was not found any kind of relation between the position on ranking of wasps and the type of resource explored by each one. Some prey samples were genetically identified, most of them belonging to order Lepidoptera (7 families). Moreover, other four orders were recognized, ...